The extreme outcomes of corporate tax management: Evidence from Chinese listed enterprises - Zhang, Chen; Cheong, Kee Cheok; Rasiah, Rajah (Faculty of Economics and Administration, University of Malaya, 2018)
This study presents an empirical analysis of how corporate tax management and government ownership influence a firm’s stock price crash risk. The study investigates firm-specific stock price crash to corporate tax management based on a sample of Chinese listed enterprises during 2008 to 2013 period and finds that tax management activities can lead to a significant decline in short-term crash risk. However, the results show that tax management would lead to the high probability of future crash risk, which is consistent with agency conflict between management and shareholders. Because of the opacity and complexity of tax management, there exists opportunities for short-term rent-seeking which can lead to future crashes. In addition, the study finds that the positive relationship between tax management and future crash risk is more pronounced in enterprises controlled by the municipal government.